Assessing Data Privacy Attitudes of Information Technology Students: Basis for Awareness Enhancement - Dela Rosa, Aaron Paul M. (Future Science / FSH-PH Publications, 2025)
In today’s digital society, the widespread use of social media and online platforms has intensified concerns about the protection of personal information. This study examined the data privacy attitudes of Information Technology (IT) students at Bulacan State University, who are among the most engaged users of digital technologies. Using a descriptive survey administered to 350 students across year levels, the study explored their awareness of privacy policies, attitudes toward data sharing, and comfort with online tracking. Results indicated that while most students expressed high concern for online privacy and rated it as highly important, many simultaneously valued the benefits of free access to social media platforms despite potential risks to their personal information, demonstrating the persistence of the privacy paradox. Students also showed discomfort with being tracked for targeted advertising, yet their reliance on Facebook and other platforms underscores vulnerabilities in privacy practices. A majority recommended that privacy awareness training be provided during their first year of study, highlighting the need for early intervention. Findings suggest that embedding privacy literacy in the IT curriculum, institutionalizing university-wide orientations, and aligning with the Philippine Data Privacy Act of 2012 are essential to building a culture of responsible data handling and compliance in higher education.